Mitochondrial unfolded protein response in regulatory T cell function: a protective mechanism in immune aging - Lewis, Lillie; Valvi, Deepa; Gedaly, Roberto; Marti, Francesc (Frontiers in Immunology, 2025)
Age-related conditions, such as neurodegenerative disease, cancer, and autoimmune disorders, are increasingly recognized as closely linked with the gradual deterioration of the immune system. Regulatory T cells (Tregs) are a small, specialized subset of T lymphocytes that play a critical role in maintaining immune homeostasis and self-tolerance. As individuals age, Treg cells demonstrate reduced capacity to suppress some autoreactive immune responses, although they largely retain their capacity to regulate effector antiviral and antitumor immunity. Unlike conventional effector T cells (Teff), which primarily derive energy from glycolysis, Tregs rely more on mitochondrial oxidative phosphorylation to fulfill their energy requirements. This metabolic profile renders them particularly sensitive to mitochondrial dysfunction, underpinning the critical role of mitochondrial protective pathways in preserving the functional integrity of Treg cells. The mitochondrial unfolded protein response (mitoUPR) is gaining special relevance among these protective mechanisms. In this review, we examine the complex interplay between immune aging and mitochondrial dynamics, with particular emphasis on the essential role of mitoUPR in supporting Treg function. We further discuss how targeting mitochondrial stress responses may offer novel therapeutic avenues for age-related diseases characterized by Treg dysfunction.